2021
DOI: 10.1021/acsami.1c00750
|View full text |Cite
|
Sign up to set email alerts
|

Microtube Surfaces for the Simultaneous Enhancement of Efficiency and Critical Heat Flux during Pool Boiling

Abstract: Boiling is an essential process in numerous applications including power plants, thermal management, water purification, and steam generation. Previous studies have shown that surfaces with microcavities or biphilic wettability can enhance the efficiency of boiling heat transfer, that is, the heat transfer coefficient (HTC). Surfaces with permeable structures such as micropillar arrays, in contrast, have shown significant enhancement of the critical heat flux (CHF). In this work, we investigated microtube stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
(64 reference statements)
0
31
0
Order By: Relevance
“…According to the theoretical analysis for active cavity sizes for nucleate boiling, [ 13 ] 5 and 12 µm cavities were chosen to initiate vapor nucleation at 11 and 5 °C wall superheats, respectively. [ 10 ] The cluster‐to‐cluster pitch was set to 2 mm based on the capillary length of water (≈2.5 mm) (Figure 1a), which has been found as an optimal distance between nucleation sites for effective separation of vapor bubbles in previous works. [ 10,14 ] On top of the microstructured surfaces, sharp blade‐like cupric oxide (CuO) nanostructures were created by sputtering a 500 nm copper layer over the microstructures followed by oxidation in an alkali solution (NaClO 2 , NaOH, Na 3 PO 4 , and deionized water with 3.75:5:10:100 wt%) at 95 °C for 2 min (SEM image in Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…According to the theoretical analysis for active cavity sizes for nucleate boiling, [ 13 ] 5 and 12 µm cavities were chosen to initiate vapor nucleation at 11 and 5 °C wall superheats, respectively. [ 10 ] The cluster‐to‐cluster pitch was set to 2 mm based on the capillary length of water (≈2.5 mm) (Figure 1a), which has been found as an optimal distance between nucleation sites for effective separation of vapor bubbles in previous works. [ 10,14 ] On top of the microstructured surfaces, sharp blade‐like cupric oxide (CuO) nanostructures were created by sputtering a 500 nm copper layer over the microstructures followed by oxidation in an alkali solution (NaClO 2 , NaOH, Na 3 PO 4 , and deionized water with 3.75:5:10:100 wt%) at 95 °C for 2 min (SEM image in Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Pool boiling is a widely used cooling technique in high heat flux applications such as integrated microelectronic devices, nuclear reactors, and space equipment. 1,2 To meet the increasing heat dissipation demands, various surface patterns have been designed and investigated to enhance pool boiling heat transfer, such as micro-pin-fin, 3 pillar, 4 micro/nano tube, 5,6 nanowire, 7 and microporous architecture. 8 Results indicate that surface wettability has significant influence on pool boiling because it affects bubble behaviors and liquid wetting state on the heating surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pool boiling is a widely used cooling technique in high heat flux applications such as integrated microelectronic devices, nuclear reactors, and space equipment. , To meet the increasing heat dissipation demands, various surface patterns have been designed and investigated to enhance pool boiling heat transfer, such as micro-pin-fin, pillar, micro/nano tube, , nanowire, and microporous architecture . Results indicate that surface wettability has significant influence on pool boiling because it affects bubble behaviors and liquid wetting state on the heating surface. Previous studies have reported that hydrophobic surfaces promote early onset of nucleate boiling (ONB), although bubbles tend to stay on hydrophobic surfaces, which leads to lower critical heat flux (CHF). On the contrary, hydrophilic surfaces delay the CHF, but they need larger superheat to initiate nucleate boiling. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, boiling heat transfer has already been utilized in the thermal management of high-power density system such as data centers, 4 high-power lighting equipment, 5 and especially for integrated electronics. 6 Flow boiling, making use of both the latent heat of phase-change and the forced convection, has been used for heat dissipation under extreme conditions such as for cooling of nuclear reactor fuel rods and for nuclear accident management. 7,8 Further enhancement of boiling heat transfer has become one of the important issues in both academic and industrial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Phase-change heat transfer methods via boiling has become one of the most hopeful solutions owing to its ultra-high heat transfer efficiency. Furthermore, boiling heat transfer has already been utilized in the thermal management of high-power density system such as data centers, high-power lighting equipment, and especially for integrated electronics . Flow boiling, making use of both the latent heat of phase-change and the forced convection, has been used for heat dissipation under extreme conditions such as for cooling of nuclear reactor fuel rods and for nuclear accident management. , …”
Section: Introductionmentioning
confidence: 99%